A product quality assurance mechanism for agricultural inputs for Uganda - CGIAR Research Program on Policies, Institutions, and Markets (2020)
In addition to a report to USAID (2019), a draft paper will be submitted to a journal in 2021. The results were disseminated through a presentation in 2020.